Effect of Sub-Bituminous Coal on Negative Charge Activity on Secondary Forest and Horticultural Land Contaminated with Pesticides in Sungai Pua, Agam - Herviyanti, Herviyanti; Maulana, Amsar; Prasetyo, Teguh Budi; Lita, Arestha Leo; Ryswaldi, Ridho (AGRIVITA Journal of Agricultural Science, 2024)
Pesticides are increasingly used to deal with crop-disrupting organisms. However, only 1% are on target, and the rest threaten agricultural ecology. This research aims to study the effect of Sub-bituminous coal (SC) on the change of negative charge activity (NCA) on two types of land, namely secondary forest (SF) and pesticide-contaminated horticultural land (HL-P). Two studies respectively used a completely randomized design (CRD) with three replications on two land types and five doses, namely: A = control or 0 t/ha [0 g SC/500 g soil]; B = 10 t/ha [2.5 g SC/500 g soil]; C = 20 t/ha [5.0 g SC/500 g soil]; D = 30 t/ha [7.5 g SC/500 g soil]; and E = 40 t/ha [10 g SC/500 g soil]. The results show that the effect of 40 t/ha SC can increase NCA on the surface of soil colloids (ΔpH) by 43% in SF and 23% in HL-P. The effect of 40 t/ha SC on the two types of land has a significant effect on increasing pH H2O, EC, CEC, and OM composition, respectively, by 0.70; 0.04 dS/m; 44.30 cmol(+)/kg and 7.60% in SF and 0.33; 0.01 dS/m; 26.89 cmol(+)/kg and 3.00% in HL-P, compared to the control.